Impact of Social Media, Electronic Word of Mouth and Customer Satisfaction on Customer Loyalty at Planetsurf Paragon Mall Semarang - Kristina Wahyu T.U, Bagas Revananda Nursepta Kristiawan; Kurniawan, Bayu; Goeltom, Henry Casandra (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The purpose of this study was to determine the effect of social media and electronic word of mouth on customer loyalty with customer satisfaction as an intervening variable at planetsurf paragon mall semarang. The population in this study were customers at planetsurf paragon mall semarang. Sampling in this study used accidental sampling technique. Data analysis and hypothesis testing in the study used structural equation modeling (SEM) analysis. The results of the direct effect hypothesis test used AMOS. The results showed that social media and e-WOM have a significant relationship to customer satisfaction. Customer satisfaction also plays an important role in mediating the influence of social media and e-WOM on customer loyalty. These findings support the importance of utilizing more effective digital strategies to improve customer perception, satisfaction, and loyalty, in order to support business sustainability.